Analysing the state of optimal motivation in endurance sports under controlled conditions - Kopp, P.; Janta, M.; Lichtenberg, C.; Senner, V. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Previous studies showed, that flow experience will occur even if there is no required balance of challenge and skills. Neither subjectively perceived fit nor objective measurements confirmed this assumption regarding a congruence of both influencing factors as a requirement for the occurrence of flow. Therefore, the aim of this study is to test whether the optimal adaption of abilities and demands will be precondition for the development of flow experiences in racing cyclists, even if it`s examined under laboratory conditions. Furthermore, it is the target to document the individual dynamics of flow during continuous cycling performances and their correlations with physiological variables. Methods: The four- week investigation (N = 10) was conducted in a climate chamber under controlled conditions (T: 18° Celsius; relative humidity: 50%; air velocity: 1m/s; uniform clothing). Therefore, flow experience should be impaired less as possible since the parameters were selected by insuring physical wellbeing independent of low or high physical stress. The individual predetermined physical strain to pass was examined by using a bicycle ergometer. Physical demands were based on an existing maximal incremental cycling test for each test subject. This allowed an individual setting of load intensity according to usual training zones (KB, GA1, GA2, EB) in cycling. The adjustment was related to the individual anaerobic threshold (IAT) as follows: KB: 55,2%; GA1: 76,7%; GA2: 92,4%; EB: 104,4. Continuous recording of physiological parameters (heart rate; pedaling frequency; wattage; power range) could be ensured at each point of time. Flow was measured with the Flow Short Scale (Rheinberg et al., 2003) close to the desired situation of optimal motivation without interrupting the applied activity at an interval of ten minutes by a verbal query (Schattke et al., 2009). Participants had an achievement-related affinity towards cycling to make flow experience more likely to occur. Results: Positive correlation between total flow score and pedaling frequency (r = 0,90) as well as heart rate (r = 0,65) . The stated balance between task difficulty and skills (M = 6,60) at the end of the EB area (high physical demands) with recognizable incongruent relationship of both factors has a higher Flow score (M = 5,75) than any stated fit in the areas EB, GA1 and GA2 with low or moderate strain. Discussion: It is possible to create Flow on a bicycle ergometer under controlled conditions within the predefined performance areas independent of any perceived balance concerning challenge and skill. Nevertheless test subjects were acquired with an imputed high implicit achievement motive and perceived importance towards cycling. Occurrence of flow however is also motivated due to more influencing intrapsychic factors we didn`t measure at all (Kehr, 2004). Physical demand were matched with the individual threshold (IAT). Results are not generalizable caused by the small sample size. Therefore Flow experience among controlled circumstances is no predictor for real terms.